2019
DOI: 10.3390/e21030317
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-Modular Connectivity Alterations in the Brain Structural Network of Spinocerebellar Ataxia Type 3

Abstract: In addition to cerebellar degeneration symptoms, patients with spinocerebellar ataxia type 3 (SCA3) exhibit extensive involvements with damage in the prefrontal cortex. A network model has been proposed for investigating the structural organization and functional mechanisms of clinical brain disorders. For neural degenerative diseases, a cortical feature-based structural connectivity network can locate cortical atrophied regions and indicate how their connectivity and functions may change. The brain network of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Finally, we included a total of 29 articles in this review. Twenty papers examined structural MRI [volumetric: n = 12 (Bürk et al, 1996;Etchebehere et al, 2001;Yoshizawa et al, 2003;Liang et al, 2009;Schulz et al, 2010;Camargos et al, 2011;D'Abreu et al, 2011;Ogawa et al, 2012;De Rezende et al, 2015;Nunes et al, 2015;Rezende et al, 2018;Jao et al, 2019b), voxel-based morphometry (VBM): n = 8 (Schulz et al, 2010;D'Abreu et al, 2012;Guimarães et al, 2013;Lopes et al, 2013;Kang et al, 2014;Hernandez-Castillo et al, 2017;Peng et al, 2019;Guo et al, 2020), and surface analysis: n = 4 (De Nunes et al, 2015;Rezende et al, 2018;Arruda et al, 2020)], seven papers examined MRS (Lei et al, 2011;Lirng et al, 2012;Wang et al, 2012;Lopes et al, 2013;Chen et al, 2014;Adanyeguh et al, 2015;Peng et al, 2019), and ten papers examined DTI (Guimarães et al, 2013;Lopes et al, 2013;Kang et al, 2014;Nunes et al, 2015;Wu et al, 2017;Rezende et al, 2018;Jao et al, 2019a;Peng et al, 2019;Meira et al, ...…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Finally, we included a total of 29 articles in this review. Twenty papers examined structural MRI [volumetric: n = 12 (Bürk et al, 1996;Etchebehere et al, 2001;Yoshizawa et al, 2003;Liang et al, 2009;Schulz et al, 2010;Camargos et al, 2011;D'Abreu et al, 2011;Ogawa et al, 2012;De Rezende et al, 2015;Nunes et al, 2015;Rezende et al, 2018;Jao et al, 2019b), voxel-based morphometry (VBM): n = 8 (Schulz et al, 2010;D'Abreu et al, 2012;Guimarães et al, 2013;Lopes et al, 2013;Kang et al, 2014;Hernandez-Castillo et al, 2017;Peng et al, 2019;Guo et al, 2020), and surface analysis: n = 4 (De Nunes et al, 2015;Rezende et al, 2018;Arruda et al, 2020)], seven papers examined MRS (Lei et al, 2011;Lirng et al, 2012;Wang et al, 2012;Lopes et al, 2013;Chen et al, 2014;Adanyeguh et al, 2015;Peng et al, 2019), and ten papers examined DTI (Guimarães et al, 2013;Lopes et al, 2013;Kang et al, 2014;Nunes et al, 2015;Wu et al, 2017;Rezende et al, 2018;Jao et al, 2019a;Peng et al, 2019;Meira et al, ...…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Module 1 in the middle-aged group contains 14 frontal nodes, 3 temporal nodes, 3 parietal nodes, and 2 occipital nodes. Module 1 contained four bilateral nodes (highlighted with underlining in Table 3 ) of the frontal lobe (CACg(L,R), CMF(L,R), Tr(L,R) and PreC(L,R)) which mainly correspond to regions associated with cognitive and executive functions [ 26 , 34 ]. Module 2 comprises 14 regions, including the frontal, temporal, parietal, and occipital lobes, which are mainly related to sensorimotor, visual, and spatial functions.…”
Section: Resultsmentioning
confidence: 99%
“…Module 2 comprises 14 regions, including the frontal, temporal, parietal, and occipital lobes, which are mainly related to sensorimotor, visual, and spatial functions. Module 3 comprises 13 nodes in the frontal, temporal, and parietal lobes, including parahippocampal (PaH), superior temporal (SM), and supramarginal (SM) regions, which may be related to mnemonic and emotional functions [ 26 ]. We found that modules 1, 2, and 4 have at least one pair of bilateral node links, and the network modularity ( Q ) value for the middle-aged group was 0.2307.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations